Lipid Nanocapsule: A Novel Approach to Drug Delivery System Formulation Development - Kumar, Parveen; Yadav, Nishant; Chaudhary, Benu; Umakanthan, Srikant; Chattu, Vijay K.; Kazmi, Imran; Al-Abbasi, Fahad A.; Alzarea, Sami I.; Afzal, Obaid; Altamimi, Abdulmalik S.A.; Gupta, Gaurav; Gupta, Madan M. (Current Pharmaceutical Biotechnology, 2024)
Nanocapsules are polymeric nanoparticles encased in a polymeric coating composed of a predominantly non-ionic surfactant, macromolecules, phospholipids, and an oil core. Lipophilic drugs have been entrapped using various nanocarriers, including lipid cores, likely lipid nanocapsules, solid lipid nanoparticles, and others. A phase inversion temperature approach is used to create lipid nanocapsules. The PEG (polyethyleneglycol) is primarily utilised to produce nanocapsules and is a critical parameter influencing capsule residence time. With their broad drug-loading features, lipid nanocapsules have a distinct advantage in drug delivery systems, such as the capacity to encapsulate hydrophilic or lipophilic pharmaceuticals. Lipid nanocapsules, as detailed in this review, are surface modified, contain target-specific patterns, and have stable physical and chemical properties. Furthermore, lipid nanocapsules have target-specific delivery and are commonly employed as a marker in the diagnosis of numerous illnesses. This review focuses on nanocapsule synthesis, characterisation, and application, which will help understand the unique features of nanocapsules and their application in drug delivery systems.
Keywords: encapsulation